2022
DOI: 10.3389/fpsyg.2022.956160
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers’ attitudes and self-efficacy beliefs for implementing student self-assessment of English as a foreign language writing

Abstract: With the growing need to nurture students’ independent learning, English language teaching (ELT) practices should reflect student-centered assessment approaches, such as self-assessment, an ultimate goal of higher education. It has been pointed out that to conduct effective self-assessment, students need to be taught systematically, and that is where teachers are expected to step in. Prior to implementing such a change in ELT, it is important to conduct research on English as a foreign language (EFL) teachers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…New teaching models based on LPS were also adopted to improve learning confidence and outcomes (Shi & Zheng, 2021;Xiong & Liu, 2020;Zhong, 2019). Students used LPS as a benchmark to provide feedback from their self-assessments, track their progress, and set learning goals (He & Zhang, 2021;Li, 2022;Zhang & Wang, 2022). The intervention of LPS in learning could help cultivate self-regulated learners and enhance students' motivation and learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New teaching models based on LPS were also adopted to improve learning confidence and outcomes (Shi & Zheng, 2021;Xiong & Liu, 2020;Zhong, 2019). Students used LPS as a benchmark to provide feedback from their self-assessments, track their progress, and set learning goals (He & Zhang, 2021;Li, 2022;Zhang & Wang, 2022). The intervention of LPS in learning could help cultivate self-regulated learners and enhance students' motivation and learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 reveals how students used CSE. Zhang and Wang (2022) explored the scaffolding role of the CSE writing scale in college students. Results showed that with the intervention of CSE, students' assessing ability, writing skills, and learning confidence were significantly improved.…”
Section: Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, self-assessment has both strengths and weaknesses. It improves learning and it is a means to understand better for what purpose the students are doing and have done a given activity or work (Zhang, 2021). With regard to the weaknesses, there are doubts that some students may not be able to pinpoint their strong and weak aspects of their work (Gazza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…False self-assessment could possibly lead to students' inaccurate understandings of their abilities, learning outcomes, and curricular expectations in the assessment process, and, over the last three decades, there has been increasing research investigating the role of self-assessment in writing at different learning levels, as self-assessment and writing performance are deemed to be as closely associated with one another [5,10,21]. Nevertheless, it is surprising to find that research on the effects of using self-assessment in the EFL contexts has not been sufficiently documented, especially in the domain of tertiary writing [29]. For instance, in western contexts, most research about student self-assessment focuses on the elementary or the secondary level [11], and empirical research on self-assessment conducted in tertiary EFL writing classrooms has received limited attention.…”
Section: Introductionmentioning
confidence: 99%